Adipose tissue macrophage heterogeneity and the role of Tim4⁺ macrophages in lipid homeostasis - Magalhaes Pinto, Marlène Sophie (The University of Edinburgh, 2019)
Resident macrophages are essential for the maintenance of tissue homeostasis as they participate in clearance of apoptotic cells and tissue remodelling and repair. In recent years, there has been an increased interest in the study of adipose tissue macrophages (ATMs). In lean individuals, ATMs are important for the control of insulin sensitivity, thermogenesis, angiogenesis and adipose tissue development. In obesity, the number and phenotype of ATMs is altered, and is associated with chronic low grade systemic and local inflammation. These “pro-inflammatory” changes are postulated to contribute to the manifestation of metabolic syndrome. These findings have suggested that the pool of ATMs is heterogeneous and may change, especially during obesity. To date, the characterisation of ATMs has been limited largely to the F4/80/CD11b markers, however the hypothesis of this thesis is that ATMs have distinct phenotype and function that could influence, in different ways, tissue homeostasis. This thesis aims to characterise and phenotype ATM subsets in order to better understand their potential specific role in the tissue. During the course of this research, a novel population of Tim4+ resident ATMs were identified. An additional aim of this thesis was to elucidate their role in adipose tissue homeostasis. Partial bone marrow chimeras were used to identify macrophage origin. The main AT depots were shielded from irradiation and a donor BM was injected intravenously. After 8 weeks, the origin of macrophages was analysed using flow cytometry. Tim4, a phosphatidylserine receptor mediating phagocytosis of apoptotic cells and a marker found on resident macrophages in other tissues, was used for the first time in adipose tissue. Four subsets of ATMs were identified: F4/80highCD11c-Tim4+, F4/80highCD11c- Tim4-; F4/80lowCD11c+Tim4-; F4/80lowCD11c-Tim4-. Interestingly, this newly described F4/80highTim4+ ATM subset showed the lowest non-host chimerism compared to the other ATMs, suggesting this is a main self-replenishing resident ATM population. To study the impact of obesity on ATM turnover, partial chimeric mice were fed HFD for 8 weeks. This increased the number of macrophages in AT. However, the different subsets of ATMs were differentially affected by the diet. Indeed, only a small proportion of Tim4+ ATMs derived from the bone marrow. In contrast, replenishment of the 3 other subsets was almost fully dependent on the arrival of monocyte-derived cells from the bone marrow. TIMD4, the gene encoding for Tim4, has been highlighted in genetic studies as being linked with dyslipidaemia. This suggests that Tim4+ ATMs might play a role in lipid homeostasis. Further characterisation of Tim4 ATMs demonstrated that these Tim4+ ATMs are highly charged in neutral lipid, and also have an increased lysosomal activity (shown by lysotracker staining) compared to the other ATM subsets. Using blocking anti-Tim4 antibodies in vivo, I found that Tim4 contributed markedly to free fatty acid (FFA) release into the plasma after short-term and long term HFD feeding. In addition, in vitro and in vivo experiments demonstrated that Tim4 could be required for the uptake of neutral lipids and their integration into lysosomes for degradation, though this seems to be dependent on the nature of the lipid. Collectively, these results indicate that Tim4 plays a crucial role in the control of lipid trafficking under conditions when dietary lipid is in excess. Tim4 allows uptake of lipids by Tim4+ ATMs and subsequent release of FFA into the circulation. Finally, the presence of Tim4+ lipid laden ATMs was demonstrated in the human omentum. This finding may lead to the discovery of new targets to improve metabolic health in obese patients. This work stresses the importance of resident ATM population in body lipid homeostasis as they could be involved in coping with lipid availability in the body and influence the amount of FFA in the plasma.
Keywords: obesity; Tim4; adipose tissue; lipid metabolism; macrophages